(untitled) (Swiss Medical Weekly, 2020)
STUDY AIM The aim of this study was to identify the prevalence of organisational structures and processes for the support of second victims in Swiss hospitals. METHODS To identify institutional policies and support for health professionals who have been involved in an adverse patient event and become traumatised from the event, also called second victims, we conducted a cross-sectional, multicentre survey study. We targeted Swiss acute care, university and psychiatric hospitals, as well as rehabilitation and speciality clinics. A 13-item questionnaire was used to collect information from hospital quality managers regarding their institutions’ policies and support practices with respect to second victims. Data were analysed using descriptive statistics. RESULTS Overall, respondents from 116 hospitals completed the questionnaire (response rate 50.2%). Most institutional respondents reported both that they would like to receive information about adverse events and that their institutions offer related support. Of participating institutions, 60% indicated that they actively inform their personnel about second-victim support possibilities; however, only 31% specifically train supervisory personnel to deliver that support, and only 32% have hospital-specific guidelines in place for second victim support. University, acute care and speciality clinics were more likely to use such guidelines than psychiatric and rehabilitation clinics. Analysis indicated an association between hospital size and the existence of guidelines. CONCLUSIONS In Swiss hospitals, second victim support is generally prevalent, but often in an unstructured way. This lack of methodology increases the risk that, following adverse events, both the quantity and quality of support provided to health professionals will be insufficient. A firm commitment on the part of institutional leaders to implement related policies could foster the adoption of high-quality second victim guidelines in Swiss hospitals.